Project-based learning in basic photography learning: The effect on student learning outcome - Saputra, Mokhamad Dwi Agung; Ulfa, Saida; Degeng, Made Duananda Kartika (Journal of Research in Instructional, 2024)
This research aims to assess the impact of implementing the project based learning on enhancing student learning outcomes in photography sessions within the visual communication design program at Vocational High School. Additionally, the study intends to compare the effectiveness of this learning with conventional learning. The study used a quasi-experimental method using a non-equivalent control group. The study was carried out at Vocational High School Muhammadiyah 1 Kepanjen. The samples in this research were X-grade students in visual communication design. They were separated into two groups: the experimental group, consisting of 17 students, and the control group, also composed of 17 students. The data was gathered by assessing students' learning outcomes before and after using the learning strategies of each group. The research utilized a portfolio of photographic project outcomes as the instrument, which included specified evaluation criteria. The data analysis in the research included a normality test, homogeneity test, and independent samples t-test. The findings indicated a notable disparity in learning outcomes between the experimental and control groups. The study findings suggest project-based learning may enhance student learning outcomes in photography sessions.